Chapter 10 Performing Scots- European heritage, 'For A' That!' - McFadyen, Mairi (Taylor & Francis, 2019)
This chapter focuses on the Scots- speaking community and, in particular, on its use of the Scots language as a means to assert political diff erence in the form of a 'welcoming, inclusive civic nationalism' (McFadyen 2018 ).